PENGARUH BRAND IMAGE, ONLINE CUSTOMER RATING DAN ONLINE CUSTOMER REVIEW TERHADAP KEPUTUSAN PEMBELIAN PRODUK KOSMETIK LUXCRIME DI SHOPEE - Suwito, Ghirrid Salsabila; Kussudyarsana (FEB Universitas Sam Ratulangi Manado, 2024)
The purpose of this study is to see the influence of Brand Image, Online Customer Review and Online Customer Rating on Purchasing Decisions on Luxcrime Cosmetic products at Shopee. This study used a quantitative approach and the data of this study used sources from questionnaires. The sampling technique uses purpose sampling technique. The researchers of this study used 273 samples using the Issac and Michael method with an error rate of 10%. The criteria for respondents in this study, users of Luxcrime cosmetic products or consumers at Shopee who have the age of 17 years and over, have purchased Luxcrime cosmetic products at least 1 (time). This study uses the Statistical Analysis of the Program for Social Science with SPSS software The results of this study, namely Brand Image, Online Customer Review and Online Customer Rating have a positive influence on the Purchase Decision of Luxcrime Cosmetic Products at Shopee.